2015
DOI: 10.1108/mbe-11-2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Look for people, not for alpha: mutual funds success and managers intellectual capital

Abstract: Purpose – This paper aims to explore whether individual intellectual capital of a fund manager allows mutual fund to outperform market. Design/methodology/approach – The sample includes 85 Russian equity funds for the period of 2013. First, Jensen’s alpha for each fund has been calculated, and then cross-sectional regression analysis has been used. While only a part of fund managers publish biographic sketches, the authors use the Heckma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…However, Naidenova et al () found an insignificant role of previous coaching experience on team performance for five top European football leagues. At the same time, Gilbert, Côté, and Mallett () reported that the combination of experience as a player and coaching education tends to increase the efficacy of the coach.…”
Section: Coaches' Direct and Indirect Impact On Team Performancementioning
confidence: 99%
“…However, Naidenova et al () found an insignificant role of previous coaching experience on team performance for five top European football leagues. At the same time, Gilbert, Côté, and Mallett () reported that the combination of experience as a player and coaching education tends to increase the efficacy of the coach.…”
Section: Coaches' Direct and Indirect Impact On Team Performancementioning
confidence: 99%
“…Malaquias and Eid Jr. (2014) indicate that this relationship could be an indication of agency con icts, given that the manager's experience could re ect speci c knowledge of the market in which he/she operates. In addition, Naidenova, Parshakov, Zavertiaeva, and Tomé (2015) identi ed that the most experienced managers are usually older than the least experienced ones, have generally been recognized by the market, and tend to be more conservative, probably because they continue applying some strategies and routines that were right in the past.…”
Section: The Manager's Experience and Fund Performancementioning
confidence: 99%
“…Investigations concerning manager characteristics from European emerging markets have been conducted extremely rarely. The paper by Naidenova, Parshakov, Zavertiaeva and Tomé (2015), who analysed human capital characteristics of managers from Russian equity funds in relation to performance, deserves a mention here. Their results indicate that individual characteristics allow obtainment of abnormal returns.…”
Section: Existing Literaturementioning
confidence: 99%